Pengaruh Kualitas Produk, Priklanan Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Di KPRI Sedar Ngancar Kabupaten Kediri - Dimas Alif Cipta Pratama (Jurnal of Management and Social Sciences, 2023)
This study aims to determine the effect of product quality (X1), advertising (X2) and service quality (X3) on consumer satisfaction (Y) at KPRI Sedar Ngancar, Kediri Regency. This type of quantitative research. Data collection techniques primary data and secondary data. The sample selection used the accidental sampling method, the number of samples in the study was obtained by 80 respondents. Data were obtained through questionnaires, interviews, and literature studies. The analysis techniques used were validity test, reliability test, classical assumption test, multiple linear regression analysis, t test, F test and coefficient of determination test. The research results obtained multiple linear regression equation Y = 1.167 + 0.323X1 + 0.402X2 + 0.215X3 and the results of the t-test variable product quality have a partially significant effect on customer satisfaction. Advertising partially significant effect on customer satisfaction. Service quality has a partially significant effect on customer satisfaction. The results of the F test obtained Fcount results with a significance value of 0.000 <0.05. From the results of the analysis it can be concluded that product quality, advertising and service quality have a simultaneous and significant effect on consumer satisfaction at KPRI Sedar Ngancar, Kediri Regency.